Gallotannins and Lactobacillus plantarum WCFS1 Mitigate High‐Fat Diet‐Induced Inflammation and Induce Biomarkers for Thermogenesis in Adipose Tissue in Gnotobiotic Mice. Issue 9 (10th April 2019) - Fang, Chuo; Kim, Hyemee; Yanagisawa, Lora; Bennett, William; Sirven, Maritza A.; Alaniz, Robert C.; Talcott, Stephen T.; Mertens‐Talcott, Susanne U.
Abstract : Scope: Intestinal microbial metabolites from gallotannins (GT), including gallic acid (GA) and pyrogallol (PG), may possess potential anti‐obesogenic properties. Lactobacillus plantarum ( L. plantarum ) found in the intestinal microbiome encodes for enzymatic activities that metabolize GT into GA and PG. Anti‐obesogenic activities of orally administered GT in the presence or absence of L. plantarum is examined in gnotobiotic mice fed a high‐fat diet (HFD). Methods and results: Germ‐free (GF) C57BL/6J mice are divided into three groups, GF control, GF gavaged with GT, and mice colonized with L. plantarum and gavaged with GT. Compared to the control, GT decreases the expressions of lipogenic genes (e.g., fatty acid synthase (FAS)) in epididymal white adipose tissue and increases thermogenic genes (e.g., nuclear factor erythroid‐2‐like 1 (Nfe2l1)) in interscapular brown adipose tissue. Intestinal colonization with L. plantarum enhances these effects, and mice colonized with L. plantarum exhibit lower levels of tumor necrosis factor‐α (TNF‐α), monocyte chemoattractant protein‐1 (MCP‐1), leptin and plasma insulin. Conclusions: Results indicate that GT and L. plantarum reduce HFD‐induced inflammation, insulin resistance, and promote thermogenesis in adipose tissue potentially through the activity of GT‐metabolizing bacterial enzymes yielding absorbable bioactive GT metabolites. These findings imply the potential role of prebiotic–probiotic interactions in the prevention of diet‐induced metabolic disorders. Abstract : Orally administered gallotannins combined with Lactobacillus plantarum mitigate high‐fat diet‐induced inflammation and insulin resistance, and induce biomarkers for thermogenesis in adipose tissue in gnotobiotic mice. These beneficial effects are associated with the activity of gallotannin‐metabolizing bacterial enzymes yielding absorbable bioactive gallotannin metabolites. This study implies the potential role of prebiotic–probiotic interactions in the prevention of diet‐induced metabolic disorders.